Literature Review: Transformasi Teknologi dan Tantangan Era Society 5.0: Studi pada Bidang Pendidikan, Konseling, dan Profesi Hukum - Rifki Ichsan Fauzi; Faiz Fauzy; Adam Gustiawan; Ines Heidiani Ikasari (CV. Multi Kreasi Media, 2024)
The Society 5.0 era brings significant changes in various fields, especially education, counseling, and the legal profession. In education, technologies such as Artificial Intelligence (AI), Internet of Things (IoT), and e learning have opened up new opportunities to improve the quality of learning, but are still faced with challenges such as the digital divide and low technological literacy. In counseling services, the use of technologies such as counseling and cybercounseling allows wider access, but also raises privacy and ethical issues. In the legal field, technologies such as Legal Tech and Smart Contracts are revolutionizing legal practice by increasing efficiency, although they present new ethical and legal issues. This article integrates findings from various studies to understand the impacts, challenges, and opportunities offered by technology in the Society 5.0 era. The results show that cross-sector collaboration, appropriate regulation, and increased digital literacy are essential to optimally utilize technology and overcome existing challenges..